Educational innovation with technology. Strategies for the promotion of learning in the digital era. Red Innova Cesal, 2024 (VITAL, 2025)
In collaboration with Red Innova Cesal, the book “Innovación educativa con tecnología” was published, which includes chapters by professors from the UAN School of Medicine on strategies such as Project Based Learning and the use of simulations for teaching semiology and emergency management, highlighting their impact on academic and clinical training.
Keywords: Innovation; Project Based Learning; Technology